Evaluasi Pembelajaran Geografi Berbasis Daring Pada Masa Pandemi Covid-19 Di Sma Negeri 2 Kota Bengkulu - Edwar Edwar; Lola Octalia; Fevi Wira Citra; haimah haimah (Universitas Prof. Dr. Hazairin, S.H, 2022)
This study aims to obtain data, process, analyze and discuss Evaluation of Online-Based Geography LearningDuring the Covid-19 Pandemic Period at SMA Negeri 2 Bengkulu City. This type of research is qualitative. Thesample in this study were geography teachers and students who took geography lessons at SMA Negeri 2Bengkulu City. Data collection techniques using observation, interviews and documentation. Data analysis wascarried out by data reduction, data presentation, and drawing conclusions. The results of this study show thatevaluating online-based geography learning, the teacher always evaluates systematically, the teacherdetermines the assessment through assignments and student attendance in online learning activities, the teacheralways tries to achieve the goals of the evaluation.